Patient perceived quality of nursing care in hemodialysis: A meta-synthesis - Abbas Balouchi; Abbas Ebadi; Soroor Parvizy; Hamid Sharif Nia (PAGEPress Publications, 2021)
This study was done with the purpose of clarifying the concept of patient perceived quality of nursing care in hemodialysis. In this meta-synthesis study, qualitative studies was searched in the four interntional databases from January 1st, 2000 to December 30th, 2019. The keywords used were: nursing care quality, and hemodialysis. Studies which had been done with the purpose of understanding the patient perceived quality of nursing care concept aomg hemodialysis patients were included. Two researchers were evaluate the quality of included studies separately using JBI tool, required information were extracted using the designed table. The main themes in the structure dimension include Sufficient Human resource, quality of equipment, financial support from patient and quality of the patient care environment. Process dimension consisted of continuous monitoring of the syndromes, effective patient education, efficient care, effective therapeutic relationship, and patient's empowerment and participation in the process, and in the outcome dimension included high dialysis adequecy, patient burnout reduction, and increased patient satisfaction from services. The results of the study indicated a comprehensive, deep and interactive dimensions about the concept of nursing quality of care.